Islam dot com contemporary Islamic discourses in cyberspace - El-Nawawy, Mohammed 1968-; Khamis, Sahar (Palgrave Macmillan series in international political communication, 2009)
This book analyzes the discourses and deliberations in the discussion forums of three of the most visited Islamic websites. In doing so, it explores the potential impact of the Islamic public sphere, and the re-configuration of the 'virtual umma' (Islamic community) online, on the creation of multiple identities and resistances, which manifest themselves through various Islamic sites, producing varying degrees of consensus, divergence, and negotiation in multiple contexts and across different discourses. The book also investigates the extent to which these Islamic websites have provided a venue for Muslims to freely engage in vibrant deliberations and constructive discussions among themselves, as well as with 'Others', i.e., non-Muslims, about various political, economic, religious and social issues.